Penerapan Model Pembelajaran Treffinger untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa berdasarkan Self-Efficacy - Nindi Eliza Putri; Abdul Fatah (Universitas Negeri Gorontalo, 2023)
In order to understand the content of mathematics, students must have an understanding of mathematical concepts. This study aims to examine how Treffinger learning can improve students' ability to understand mathematical concepts in terms of self-efficacy. This type of quantitative research is an approach designed for this experimental research. Class VII students of MTsN 1 Pandeglang are the population or object under study. The research design applied to the study was the Pretest-Posttest Nonequivalent Control Group Design. Sampling was determined using purposive sampling technique, class VII B and VII F were selected to serve as the experimental class and control class. Validated questionnaires and tests are useful research tools for collecting data on students' self-efficacy and ability to understand mathematical concepts. The hypothesis test in this study applies the Two-Way ANOVA test. The results of the study revealed that the Treffinger learning model provided an increase in the ability to understand mathematical concepts. What's more, there is a contribution between self-efficacy towards students' understanding of mathematics concepts.